Senandung Tak Bertahta Exhibition in the Frame of Socialist Realism Pramoedya Ananta Toer - Jaya Putra, I Gede; Wulansari, Vita; Devi Krishnanandayani, Jyothi (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2025)
This article discusses about Senandung tak Bertahta exhibition which departs from the situation and conditions of Balinese society in the frame of socialist realism Pramoedya Ananta Toer. Balinese society is still struggling to meet their living needs behind the glittering tourism sector. Take for example the Kerobokan area of Bali which is always under pressure with the rate of growth, between struggling, surviving, actually giving up, especially on the issue of land which is squeezed and lured by investors' enticements. The data source was obtained through a qualitative approach using a descriptive analysis method by utilizing library media. The Senandung tak Bertahta exhibition is a representative to voice the phenomenon, through three works that represent the voices of the buried community, the context of body ownership and the issue of fake identity. The Senandung tak bertahta exhibition will be studied using the theory of Socialist Realism which is in line with Pramoedya's thoughts and the works will be studied using theories by Adorno, Foucault and Julia Kristeva which describe the problem of the helplessness of society which is in line with the context of socialist realism. By studying symbolic elements, visual composition, and social context, this exhibition shows how contemporary art is still relevant as a medium for the struggle of lower-class discourse, as proposed in Pramoedya's literature.